ATTITUDE OF QUEEN ZALEHA THE WOMAN WARRIOR OF SOUTH KALIMANTAN - Kamariah Kamariah; Haswinda Harpriyanti (Jurusan Sastra Indonesia, 2019)
This study aims to describe Queen Zaleha attitude during his life when facing the war of independence. The research method uses qualitative methods with descriptive research specifications, the research object of the life story of Queen Zaleha. The data collection techniques used are notes, interviews, and documentation. Techniques analysis use the semiotic model of Roland Barthes. The results showed that Queen Zaleha's stance was: a) conscious, b) clever, c) brave, d) fighting spirit, e) confident.